Evaluating pain in survivors of critical illness: the correlation between the EQ-5D-5L and the Brief Pain Inventory. Issue 1 (18th January 2023) - Docherty, Christie; Shaw, Martin; Henderson, Philip; Quasim, Tara; MacTavish, Pamela; Devine, Helen; O'Brien, Peter; Strachan, Laura; Lucie, Phil; Hogg, Lucy; Sim, Malcolm; McPeake, Joanne
Abstract : Introduction: Pain is a common and debilitating symptom in survivors of critical illness. The 'Core Outcome Set for Survivors of Acute Respiratory Failure' proposes that the pain and discomfort question of the EuroQol 5 Dimension 5 Level (EQ-5D-5L) could be used to assess pain in this group, however, it was recognised that further research is required to evaluate how this single question compares to other more detailed pain tools. This study aims to evaluate the relationship between the pain and discomfort question of the EQ-5D-5L and the Brief Pain Inventory (BPI) in survivors of critical illness. Methods: This study retrospectively analysed paired EQ-5D-5L and BPI data extracted from a prospective, multicentre study evaluating the impact of a critical care recovery programme. 172 patients who received a complex recovery intervention and 108 patients who did not receive this intervention were included. Data were available for the intervention cohort at multiple time points, namely, baseline, 3 months and 12 months. While, data were available for the usual care cohort at a single time point (12 months). We assessed the correlation between the pain and discomfort question of the EQ-5D-5L and two separate components of the BPI: severity of pain and pain interference. Results: Correlation coefficients comparing the pain and discomfort question of the EQ-5D-5L and the BPI pain severity score ranged between 0.73 (95% CI 0.63 to 0.80) and 0.80 (95% CI 0.72 to 0.86). Correlation coefficients comparing the pain and discomfort question of the EQ-5D-5L and the BPI pain interference score ranged between 0.71 (95% CI 0.62 to 0.79) and 0.83 (95% CI 0.76 to 0.88) across the various time points. Conclusions: The pain and discomfort question of the EQ-5D-5L correlates moderately well with a more detailed pain tool and may help to streamline assessments in survivorship studies. More in-depth tools may be of use where pain is the primary study outcome or a patient-reported concern.